Formula:5193

From MaRDI portal

Digital Library of Mathematical Functions ID 13.14.E7

lim 2 μ - n - 1 M κ , μ ( z ) Γ ( 2 μ + 1 ) = ( - 1 2 n - κ ) n + 1 ( n + 1 ) ! M κ , 1 2 ( n + 1 ) ( z ) = e - 1 2 z z - 1 2 n s = n + 1 ( - 1 2 n - κ ) s Γ ( s - n ) s ! z s . subscript 2 𝜇 𝑛 1 Whittaker-confluent-hypergeometric-M 𝜅 𝜇 𝑧 Euler-Gamma 2 𝜇 1 Pochhammer 1 2 𝑛 𝜅 𝑛 1 𝑛 1 Whittaker-confluent-hypergeometric-M 𝜅 1 2 𝑛 1 𝑧 superscript 𝑒 1 2 𝑧 superscript 𝑧 1 2 𝑛 superscript subscript 𝑠 𝑛 1 Pochhammer 1 2 𝑛 𝜅 𝑠 Euler-Gamma 𝑠 𝑛 𝑠 superscript 𝑧 𝑠 {\displaystyle{\displaystyle\lim_{2\mu\to-n-1}\frac{M_{\kappa,\mu}\left(z% \right)}{\Gamma\left(2\mu+1\right)}=\frac{{\left(-\frac{1}{2}n-\kappa\right)_{% n+1}}}{(n+1)!}M_{\kappa,\frac{1}{2}(n+1)}\left(z\right)=e^{-\frac{1}{2}z}z^{-% \frac{1}{2}n}\sum_{s=n+1}^{\infty}\frac{{\left(-\frac{1}{2}n-\kappa\right)_{s}% }}{\Gamma\left(s-n\right)s!}z^{s}.}}


Constraint(s)

Symbols List

Resources that cite this formula

No records found.